Development of Seed Keys for Varietal Identification in Rice (Oryza sativa) using Chemical Tests - B. VIJAYALAKSHMI; D. VIJAY (Seed Research, 2026)
The decrease in the morphological variation among the major rice varieties due to narrow genetic base makes it necessary for the development of quick and reliable tests for varietal identification particularly for those working in seed certification and quality maintenance. Twenty three genotypes of rice were tested for five different chemical tests viz., Phenol, Modified Phenol, NaOH, FeSO, and KOH tests. Based on the colour reaction of different genotypes seed keys were developed for distinguishing the twenty three paddy varieties. All the five chemical tests grouped the varieties into two to four classes based on their reaction. Even though, not even a single test could identify any individual variety, but in conjunction the five chemical tests identified all the twenty three rice varieties individually. Thus these simple, reliable and quick tests can be used for varietal identification in rice crop.